2021
DOI: 10.3390/cancers13081748
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of AHNAK2 Expression in Patients Treated with Radical Cystectomy

Abstract: Data regarding expression levels of AHNAK2 in bladder cancer (BCa) have been very scarce. We retrospectively reviewed clinical data including clinicopathological features in 120 patients who underwent radical cystectomy (RC) for BCa. The expression levels of AHNAK2 in the specimens obtained by RC were classified as low expression (LE) or high expression (HE) by immunohistochemical staining. Statistical analyses were performed to compare associations between the two AHNAK2 expression patterns and the prognoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Discordant cases were reviewed and discussed until a consensus was reached. AHNAK2 (HPA004145; Sigma-Aldrich, St. Louis, MO, USA) immunohistochemical staining was performed as previously described [39]. To better understand the mechanism of action of S100A16 in BC, we analyzed the association between S100A16 and AHNAK2.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
“…Discordant cases were reviewed and discussed until a consensus was reached. AHNAK2 (HPA004145; Sigma-Aldrich, St. Louis, MO, USA) immunohistochemical staining was performed as previously described [39]. To better understand the mechanism of action of S100A16 in BC, we analyzed the association between S100A16 and AHNAK2.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
“…They found that patients with high AHNAK2 expression had significantly lower recurrence-free survival (RFS) and cancer-specific survival (CSS). Multifactorial analysis showed that high AHNAK2 expression could be an independent risk factor for worse RFS and CSS ( 101 ). A similar conclusion was reached in another study in which Komina et al.…”
Section: Relationship Between Ahnak Family and Tumor Developmentmentioning
confidence: 99%
“…They found that patients with high AHNAK2 expression had significantly lower recurrencefree survival (RFS) and cancer-specific survival (CSS). Multifactorial analysis showed that high AHNAK2 expression could be an independent risk factor for worse RFS and CSS (101). A similar conclusion was reached in another study in which Komina et al collected urine samples from 67 cancer patients with bladder occupancy (bladder cancer group N=37, benign bladder tumors N=30) and found that the mean urinary AHNAK2 protein level was almost 10 times higher in bladder cancer patients than that in controls (49.08 pg/mL vs. 5.28 pg/mL) and that AHNAK2 expression level in invasive bladder cancer was significantly higher than that in non-invasive bladder cancer (117.99 pg/mL vs. 7.14 pg/mL).…”
Section: Bladder Cancermentioning
confidence: 99%
“…Koguchi et al 2021 [27] evaluate the expression of AHNAK2 (AHNAK Nucleoprotein 2), a protein coding gene, that has been identified as a possible tumor marker and therapeutic target in different malignancies including clear cell renal cell carcinoma, papillary thyroid carcinoma, lung and pancreatic duct adenocarcinoma, and others. Their study of 120 patients with bladder cancer undergoing radical cystectomy finds an association between high AHNAK2 expression and classical aggressive pathologic findings, but also as an independent prognostic marker for recurrence-free survival and disease-specific mortality in this set of patients [27]. Chen et al [28] investigate S1PR1 expression, a G protein-coupled receptor in vascular endothelial and immune cells.…”
Section: Bladder Cancermentioning
confidence: 99%